How to Test Molyneux's Question Empirically. (December 2013) - Connolly, Kevin
In a recent i-Perception article, Schwenkler (2012 ) criticizes a 2011 experiment by R. Held and colleagues purporting to answer Molyneux's question. Schwenkler proposes two ways to re-run the original experiment, either by allowing subjects to move around the stimuli, or by simplifying the stimuli to planar objects rather than three-dimensional ones. In Schwenkler (2013 ), he expands on and defends the former. I argue that this way of re-running the experiment is flawed, since it relies on a questionable assumption that newly sighted subjects will be able to appreciate depth cues. I then argue that the second way of re-running the experiment is successful both in avoiding the flaw of original Held experiment, and in avoiding the problem with the first way of re-running the experiment.